β-Guanidinopropionic acid as the secondary components in the co-assembly strategy for inverted perovskite solar cells - Yinfeng Zhang; Xinyi Wu; Wenjing Peng; Mei Lyu; Jun Zhu (Next Energy)
Amphiphilic self-assembled molecules (SAMs) that incorporate carbazole core and phosphonic acid have demonstrated significant potential for enhancing the power conversion efficiency (PCE) and stability of inverted perovskite solar cells (PSCs). However, SAMs can easily form micelles in alcohol solvents, leading to deposition on rough substrates as clusters. This clustering results in voids within the SAM layer, enabling direct contact between the perovskite active layer and the electrode, which severely undermines the efficiency and stability of the PSCs. Thus, creating a dense and uniform monolayer plays a key role in improving the performance of inverted PSCs. Here, a co-assembled monolayer (Co-SAM) was fabricated using a one-step deposition process, wherein β-guanidinopropionic acid (β-GUA) was incorporated into [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz). On the one hand, the co-assembly strategy facilitated the formation of high-quality, uniformly distributed Co-SAM. On the other hand, the guanidine group, serving as a functional head group, provides multiple passivation effects at the buried interface of the perovskite and improves the surface morphology of the perovskite films. Consequently, the Co-SAM-treated PSC achieved a champion PCE of 23.20%, with a satisfactory filling factor (FF) of 86.27%. This work offers an insight into the design of small molecule structures for the secondary SAM components in the Co-SAM strategy.